ATTITUDE OF HEARING IMPAIRED STUDENTS TOWARDS THEIR PARENTS AND TEACHERS CONCERN ON THEIR ADOLESCENT PROBLEMS AND ADJUSTMENT- A STUDY - Rekha, M. Nirmala (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The period of adolescence is one of the continued changes and transition which underlines both positive and negative out comes. The multiples biological, Psychological and Socio-Cultural changes leads them to a greater risk. Adolescents are rarely considered a distinct group with special needs. There is a lack of attention in almost every dimension of their problems. Whatever knowledge they have is incomplete and are in a confused state. Therefore Adolescents need guidance, counseling and education as well as opportunity to explore their life for themselves in order to attain a level of maturity required, to make responsible decisions. If it is not properly handled, it will have a drastic effect in the coming stages of their life. The problems which are faced by the hearing Adolescents are social problems, Psychological problems, school problems, family problems, and Physical problems. Among all the problems the family problems as well as school problem will have an adverse effect on the personality of the Adolescents. The constant interference and advice of the family members cause complex problems. Such situations should be carefully handled in order to prevent the Adolescents from becoming social miscreants. Therefore the parents must see that their adolescent children become self-reliant, Judge their own doings.